BIO GIS 360 uno strumento per il contrasto ai cambiamenti climatici e alla perdita di biodiversità - Caroselli , Valerio (GEOmedia, 2022)
Biodiversity - the diversity of all ecosystems and natural species - is being lost at an unprecedented rate of growth. According to the World Wildlife Fund's recent Living Planet report, populations of mammals, birds, fish, reptiles and amphibians have declined by an average of 60 percent in just over 40 years. Scientists Gerardo Ceballos, Paul R. Ehrlich and Rodolfo Dirzo have dubbed this decline and the impending wave of extinctions a “biological annihilation.